Species concepts and functional aspects of cold-water diatoms (Bacillariophyceae) - Degerlund, Maria (University of Tromsø, 2011)
The papers of this thesis are not available in Munin: 1. Degerlund M and Eilertsen HC: 'Main species characteristics of phytoplankton spring blooms in NE Atlantic and Arctic waters(68–80°N)', Estuaries and Coasts (2010) 33: 242-269. Available at http://dx.doi.org/10.1007/s12237-009-9167-7 2. Eilertsen HC and Degerlund M: 'Phytoplankton and light during the northern high-latitude winter', Journal of Plankton Research (2010) 32: 899-912. Available at http://dx.doi.org/10.1093/plankt/fbq017 3. Degerlund M, Huseby S, Zingone A, Sarno D and Landfald B: 'Functional diversity in cryptic species of Chaetoceros socialis Lauder (Bacillariophyceae)' (submitted paper to Journal of Plankton Research). 4. Huseby S, Degerlund M, Zingone A and Hansen, E: 'Metabolite fingerprinting and physiology of the cryptic diatom Chaetoceros socialis Lauder' (manuscript) The choice of species concept when delineating phytoplankton species is decisive for our knowledge of species diversity and distribution, but will also affect our understanding of the functioning of marine ecosystems. This is particularly true for so-called cryptic species, which may show high degree of genetic and physiological heterogeneity although being morphologically similar. A precise species delimitation procedure appreciating the value of genotypic as well as phenotypic traits is therefore important. In this thesis, species concepts and functional aspects in abundant cold-water diatoms were investigated using biogeographic (species presence and abundance), taxonomic (morphological and molecular data), and functional (experimental physiological and metabolomics data) tools. A compilation of multiannual phytoplankton species abundance data gathered during the spring bloom period from north-east Atlantic and Arctic waters (68-80oN) revealed high similarities in associations of the most abundant species. Spring associations were dominated by the diatom Chaetoceros socialis and the prymnesiophyte Phaeocystis pouchetii. A corresponding investigation of the winter ...